2017
DOI: 10.1186/s40900-017-0076-9
|View full text |Cite
|
Sign up to set email alerts
|

Strength in Numbers: an international consensus conference to develop a novel approach to care delivery for young adults with type 1 diabetes, the D1 Now Study

Abstract: Plain English summaryMany young adults with type 1 diabetes struggle with the day-to-day management of their condition. They often find it difficult to find the time to attend their clinic appointments and to meet with their diabetes healthcare team. Young adults living with type 1 diabetes are not routinely involved in research that may help improve health services other than being invited to take part in studies as research participants. A 3-day international conference was held in Galway in June 2016 called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Perhaps one of the largest examples of patient engagement in T1D research is the D1 Now study in Ireland (134, 135). This project recruited a young adult panel as co-investigators who were involved in writing grants, organizing a large international workshop, writing plain English summaries in journal articles and promoting the study using social media outlets.…”
Section: Patient-oriented Research Within the Field Physical Activitymentioning
confidence: 99%
“…Perhaps one of the largest examples of patient engagement in T1D research is the D1 Now study in Ireland (134, 135). This project recruited a young adult panel as co-investigators who were involved in writing grants, organizing a large international workshop, writing plain English summaries in journal articles and promoting the study using social media outlets.…”
Section: Patient-oriented Research Within the Field Physical Activitymentioning
confidence: 99%
“…The D1 Now study team has demonstrated that it is both feasible and desirable to include a PPI panel of young adults with T1D in health research 27,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Phase 4: Information sharing symposium and expert panel consensus meeting In June 2016, a 3-day event was organised in Galway, Ireland, entitled: 'Strength in Numbers: Teaming up to improve the health of young adults with type 1 diabetes' 29 . The overall aim of the Strength in Numbers event was to exchange knowledge and experiences among stakeholders to gain input into the D1 Now intervention development process.…”
Section: Phase 1: Formation Of a Young Adult Panel (Yap)mentioning
confidence: 99%
“…In June 2016, a 3-day event was organised in Galway, Ireland, entitled: 'Strength in Numbers: Teaming up to improve the health of young adults with type 1 diabetes' 29 . The overall aim of the Strength in Numbers event was to exchange knowledge and experiences among stakeholders to gain input into the D1 Now intervention development process.…”
Section: Phase 4: Information Sharing Symposium and Expert Panel Consmentioning
confidence: 99%
“…Reflections on the user-centred approach within D1 Now intervention development Engaging with key stakeholders is recommended as best practice for effective intervention development 10,13 and researchers are increasingly encouraged to adopt a PPI framework within health research. The D1 Now study team has demonstrated that it is both feasible and desirable to include a PPI panel of young adults with T1D in health research 27,29 .…”
Section: Building Relationships Between Young Adults and Service Provmentioning
confidence: 99%